Comparative Predation Efficiency of Betta Fish (Betta splendens) and Golden Cichlid (Melanochromis auratus) Against Aedes aegypti Larvae [Accepted] - Ningrum, Prehatin Trirahayu; Prasetiyanti, Nova Dwi; Pujiati, Rahayu Sri (Health Dynamics, 2026)
Introduction: The diseases caused by some vectors, such as dengue, malaria, chikungunya, and filariasis are still being an issue. In 2019 the Larva Free Index (LFI) in Indonesia showed a percentage of 79,2% and this number has not reached the target of the ABJ program of > 95%, with 138,127 dengue cases recorded. In order to prevent mosquito larvae, biological control is used with mosquito’s natural enemy. This research aims to identify the differences abilities between the Betta Fish and the golden cichlid as the mosquito larvae of Aedes aegypti control. Methods: This type of research was quasi-experimental with a completely randomized design (CRD). The data collected by observation. Repetition/replication in this study was 18 samples. The data analysis used an Independent T-Test with a confidence level of 95% (α = 0.05). Result and Discussion: Betta fish has ability to prey on 20 larvae within onehour, total amount of larvae eaten in 9 times repetition was 175 larvae (96.4%). The golden cichlid has the capability to prey on 18 larvae within one hour, with the total amount of larvae eaten 9 times repetitions was 146 mosquito larvae (80.6%). Betta fish had a higher predation ability than golden cichlid (p value = 0.000). Conclusion: There was a difference in the ability of Betta fish and golden cichlid to control Aedes aegypti mosquito larvae (p value = 0.000). Betta fish was able to be more effective predators of mosquito larvae than golden cichlid.